Pengembangan Aplikasi Safety Flying Drone Map (Syndrone Map) pada Perangkat Mobile Android dengan Menggunakan Metode Spatial Multi-Criteria Evaluation - Lukas Sada Arihta Sinulingga; Fatwa Ramdani; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Drone becomes a popular hobby among drone community lately. Because it can be flown and operated from the distance, many drone pilots use this technology in many sectors for their work. Because of that reason, the regulation about flying drone are needed.The Indonesian Goverment have been released a regulation about drone area into several categories, (i.e prohibited area, restricted area, safety flight operation zone, controlled airspace and uncontrolled airspace). However because many drone pilots have lack of information about the regulation that been released, many cases cause drone accident. As example drone get crashed into airplane, or drone get stucked on the building rooftop, and many more. With Geo Information System (GIS), offers several solutions like Spatial Multi-Criteria Evaluation. With this method, factors that cause a problem become criteria and parameters hierarchically, and then compose together to become a new spatial model that contains information and recommendation. For furthermore this model can be implemented on mobile application, so drone Penggunas can obtain an information from this apps. In the future this research hopefully could decrease many drone cases. From accuracy assessment, this model have 62.5% overall accuracy. This mean that 62% of the info generated from this model is in suitable with the facts in the field.